2014
DOI: 10.1007/s00404-014-3396-0
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial preparation protocol of the frozen-thawed embryo transfer in patients with polycystic ovary syndrome

Abstract: The mean endometrial thickness, clinical pregnancy rate, ongoing pregnancy rate, live birth rate and implantation rate were similar in artificial and stimulated cycle for endometrial preparation prior to FET in PCOS. It was fine to add vaginal 17-β oestradiol to stimulated cycle when necessary. However, stimulated cycles had a significantly higher cancelled cycle rate. We should follow the principles of individualization, securitization and optimization in endometrial preparation of the FET in patients with PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 41 publications
4
37
0
Order By: Relevance
“…There was no difference in clinical pregnancy rate (41.0 % vs. 41.6 %), ongoing pregnancy rate (36.6 % vs. 34.7 %) and live birth rate (30.0 % vs. 31.7 %) between two groups simillar to our study (19). Cochrane meta-analysis (2008) reported that there was no preference for methods to another (10).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…There was no difference in clinical pregnancy rate (41.0 % vs. 41.6 %), ongoing pregnancy rate (36.6 % vs. 34.7 %) and live birth rate (30.0 % vs. 31.7 %) between two groups simillar to our study (19). Cochrane meta-analysis (2008) reported that there was no preference for methods to another (10).…”
Section: Discussionsupporting
confidence: 59%
“…In a different study artificial cycle was compared with stimulated cycle which was induced by HMG for endometrial preparation prior to FET(19). There was no difference in clinical pregnancy rate (41.0 % vs. 41.6 %), ongoing pregnancy rate (36.6 % vs. 34.7 %) and live birth rate (30.0 % vs. 31.7 %) between two groups simillar to our study (19).…”
Section: Discussionmentioning
confidence: 99%
“…Of the four studies included, two are RCTs [60,61] and the remaining two are retrospective cohort studies [53,58]. These data suggest that mild stimulation with either Gn or AI may overcome subtle defects in folliculogenesis, potentially correct luteal phase, and hence improve endometrial receptivity.…”
Section: Discussionmentioning
confidence: 97%
“…A total of four studies, two RCTs [60,61] and two retrospective cohort studies [53,58], making a total of 1850 ET cycles, were included.…”
Section: Ac (With or Without Suppression) Versus Mild Os With Gn Or Amentioning
confidence: 99%
“…In a study by Gelbaya et al (56), the natural cycles and downregulated artificial cycles did not differ from each other in this respect. Clinical pregnancy, ongoing pregnancy, and live birth rates have not been found to differ between endometrial preparations induced by human menopausal gonadotrophin (HMG) or by exogenously administered estrogen-progesterone in patients with polycystic ovary syndrome (PCOS) or those with anovulation; however, a thin endometrium was more frequently observed in HMG-induced cycles (57,58). Some studies have shown that long-term GnRH agonist administration before IVF/ICSI in infertile women with endometriosis or adenomyosis significantly increases the chances of pregnancy (59).…”
Section: Which Methods Is Preferable?mentioning
confidence: 99%